The Effect of Communication, Motivation, Physical Work Environment and Non-Physical Work Environment on Performance of Employees of the Regional Disaster Management Agency of Labuhanbatu Regency - Ibrahim Ibrahim; Junita Lubis; Yudi Prayoga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research was conducted at the Regional Disaster Management Agency of Labuhanbatu Regency, with the aim of knowing the effect of communication, motivation, physical work environment and non-physical work environment on employee performance. This study uses quantitative methods, with several analytical techniques such as classical assumption test, multiple linear regression test, hypothesis testing and coefficient of determination test. All hypotheses in the study are declared valid, can be proven by the following description, the communication variable (X1) has a value of tcount (3.79) > ttable (1.66) which means Ha is accepted and Ho is rejected, thus it can be concluded that the variable communication (X1) has a positive and significant effect on employee performance. The motivation variable (X2) has a value of tcount (4.06) > ttable (1, 66) which means Ha is accepted and Ho is rejected, thus it can be concluded that motivation (X2) has a positive and significant effect on employee performance. The physical work environment (X3) has a value of tcount (5.05) > ttable (1.66) which means Ha is accepted and Ho is rejected, thus it can be concluded that the physical work environment (X3) has a positive and significant effect on employee performance. The non-physical work environment (X4) has a value of tcount (8.95) > ttable (1.66) which means Ha is accepted and Ho is rejected, thus it can be concluded that the non-physical work environment (X4) has a positive and significant effect on performance. employee. The F test results show the Fcount value of 147.44 > Ftable 2.48, from these results, it can be concluded that communication, motivation, physical work environment.